Charlie Cook's Favourite Book - Donaldson, Julia (Macmillan Publishers Ltd, 2005)
Once upon a time there was a boy called Charlie Cook who curled up in a cosy chair and read his favourite book$1! =s
Keywords: Juvenile Fiction